Effect of Force molting method on Egg quality parameters - Alfituri عواطف محمود; Sherif بشير محمد; BenMahmoud زياد الطاهر (Journal of Pure & Applied Sciences, 2022)
Estimation This study was conducted in the laboratories of the Faculty of Agriculture at Misurata University. A total of 120 fresh eggs were collected from laying hens of commercial hybrids Hy-Line With36 strain. Then, samples were divided into two groups, The first group (WN) included 60 eggs from non-molting laying hens aged 16 months, and the second group (WM) included 60 eggs from Force-molted laying hens aged 10 months in the second cycle. The eggs were numbered and the external quality was estimated by weighing each egg, egg shape index (longitudinal and transverse axis), shell thickness, internal quality estimation by the thick albumen height, yolk index, and yolk color estimation. The results illustrated that there were significant differences in the egg weight and egg shape index of forced non-molting laying hens at the level of significance (P>0.05). There was a direct relationship between the egg’s weight, the shell’s thickness, and the age of the hen, as well as the presence of a direct relationship between the height of the thick albumen height to estimate the Haugh unit with both the weight and the shape index of the egg. The compulsively Force-molted was significantly better than the non-molting laying hens, and the yolk index was suitable for the specifications of the standard extra fresh egg for the Force-molted and non-molting laying hens. There were no significant differences between the colors of the yolk in the Force-molted and non-molting laying hens due to the similarity of feeding.